Preliminary design concept for startups: minimum viable user experience - Haque, Tanzimul; Ibrahim, Shauki Ibna; Sumaiya, Maisha; Tithi, Afreen Rahman (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.